2020
DOI: 10.1097/md.0000000000022408
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of HIV positive patients with lymphoma in an oncological reference center in Mexico City

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In addition, HIV patients with HL have a relatively higher T CD4 + count and a lower viral load at diagnosis than patients with non-HL. [ 28 ] It has been suggested that the use of interperiod ART and the late timing of HL diagnosis are directly related. There are several particular characteristics of HL associated with HIV, including: advanced-stage disease (Ann Harbor III-IV), frequent constitutional symptoms, less favorable histology, more frequent bone marrow involvement, and worse prognosis compared to immunocompetent individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HIV patients with HL have a relatively higher T CD4 + count and a lower viral load at diagnosis than patients with non-HL. [ 28 ] It has been suggested that the use of interperiod ART and the late timing of HL diagnosis are directly related. There are several particular characteristics of HL associated with HIV, including: advanced-stage disease (Ann Harbor III-IV), frequent constitutional symptoms, less favorable histology, more frequent bone marrow involvement, and worse prognosis compared to immunocompetent individuals.…”
Section: Discussionmentioning
confidence: 99%
“…They usually present to care with severe immunosuppression; most of them have a recent HIV diagnosis, have not yet been linked to medical care and are naïve to antiretroviral therapy (ART) at the time of cancer diagnosis. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…They usually present to care with severe immunosuppression; most of them have a recent HIV diagnosis, have not yet been linked to medical care and are naïve to antiretroviral therapy (ART) at the time of cancer diagnosis. 3,4 This study aimed to describe the characteristics of patients who were received at the Cancer and AIDS Clinic of INCan, before and after March 2020, and to compare their clinical conditions upon first consultation, 30 and 90-day mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a significant number of patients are ART‐naïve and have low CD4 counts at the time of lymphoma diagnosis. This coupled with lack of social support contributes to poor outcomes similar to that of pre‐HAART era 5–7 …”
Section: Introductionmentioning
confidence: 99%
“…This coupled with lack of social support contributes to poor outcomes similar to that of pre-HAART era. [5][6][7] In the HAART era, outcomes of AIDS-related diffuse large B-cell lymphoma (DLBCL) when treated with CHOP (cyclophosphamide, hydroxydaunorubicin, vincristine and prednisone) did show an improvement; however, remained inferior to their immunocompetent counterparts. 8 Addition of rituximab to CHOP, failed to show improvement in overall survival (OS) of these patients.…”
Section: Introductionmentioning
confidence: 99%